Incorporating clonality into the plant ecology research agenda - Klimešová, Jitka; Ottaviani, Gianluigi; Charles-Dominique, Tristan; Campetella, Giandiego; Canullo, Roberto; Chelli, Stefano; Janovský, Zdeněk; Lubbe, F Curtis; Martínková, Jana; Herben, Tomáš (Trends in plant science, 2021)
A longstanding research divide exists in plant ecology: either focusing on plant clonality, with no ambition to address nonclonal plants, or focusing on all plants, ignoring that many ecological processes can be affected by the fact that some plants are clonal while others are not. This gap cascades into a lack of distinction and knowledge about the similarities and differences between clonal and nonclonal plants. Here we aim to bridge this gap by identifying areas that would benefit from the incorporation of clonal growth into one integrated research platform: namely, response to productivity and disturbance, biotic interactions, and population dynamics. We are convinced that this will provide a roadmap to gain valuable insights into the ecoevolutionary dynamics relevant to all plants.
Keywords: Plants; populační dynamika; ekologie; clonality; plant functions; belowground organs; Population Dynamics; rostliny; Ecology; ekosystém; Ecosystem